Ayat-Ayat Perdamaian dalam Tafsir Al-Azhar Perspektif Teori Double Movement Fazlurrahman - Iftahul Digarizki (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2021)
Religion is often used as an excuse for the emergence of conflicts, but is every conflict that occurs really on the pretext of religion? In the last few decades, conflicts on the pretext of religion have â€œbrokenâ€ in several parts of Indonesia. In addition, religion is full of equal values â€‹â€‹and norms with the term â€œpeaceâ€. Hamka is a religious figure, humanist, and writer whose most of his writings are dedicated to improving the moral aspects of human beings. In this study, the author uses the theory of double movement to analyze Hamka's intention in explaining QS. Al-Hujurat [49]:9-10. In collecting of data, the author uses a library research approach. The results of this study are from the first step of reconstructing Hamka's interpretation by taking the moral ideals contained in QS. al-Hujurat :9-10 namely Justice, tolerance, mutual help, interrelationship deliberation, and the spirit of humanity. From these values â€‹â€‹the author develops them into two forms, first, â€œinward movementâ€ as a logical consequence of self-defense from immaturity in taking a stance that triggers division. Second, the â€œoutward movementâ€ is the impact of the depth of science and spirituality so that it can be a "medicine for the soul" in social life, especially in this era of technological progress.